Traditional Chinese medicine prescriptions (XJZ, JSS) ameliorate spleen inflammatory response and antioxidant capacity by synergistically regulating NF-κB and Nrf2 signaling pathways in piglets - Chen, Jian; Hu, Nianqing; Mao, Yaqing; Hu, Aiming; Jiang, Wenjuan; Huang, Aimin; Wang, Yun; Meng, Puyan; Hu, Mingwen; Yang, Xiaobin; Cao, Yuandong; Yang, Fan; et al. (Frontiers in Veterinary Science, 2022)
Weaning transition generally impairs the immune system, inducing immune disturbance, which may be associated with post-weaning diarrhea and high mortality in piglets. The spleen is a pivotal lymphatic organ that plays a key role in the establishment of the immune system. Traditional Chinese medicine (TCM) prescriptions, XiaoJianZhong (XJZ) and Jiansananli-sepsis (JSS), are widely used prescriptions for treating spleen damage and diarrhea. Here, we hypothesized that XJZ and JSS maintain the spleen physiological function by ameliorating antioxidant capacity and inflammatory response in weaned piglets. In this study, 18 weaned piglets were assigned to the Control, XJZ and JSS groups. By hematoxylin and eosin staining, hematological analysis, flow cytometric analysis, qRT-PCR and western blot, the effects of both TCM prescriptions on the spleen antioxidant defense system and inflammatory pathway were explored. Results showed that both TCM treatment significantly ameliorated the weaning-induced morphological damage in piglets, as evidenced by clearer and more perfect spleen histology, as well as higher relative area of white pulp. Meanwhile, both XJZ and JSS exerted better blood parameters, as supported by the changes of monocyte level and lymphocyte subpopulations CD4+/CD8+ ratio. Furthermore, the levels of inflammatory markers, IL1β, IL6, IL8, and TNF-α in the spleen were markedly decreased after supplemented with both TCM prescriptions. Importantly, the inhibition of nuclear factor-kappaB (NF-κB) and its downstream effector genes (IL6, IL8, and TNF-α) in both XJZ and JSS treatment groups further confirmed alleviation of inflammatory responses in the spleen. In addition, both XJZ and JSS enhanced the antioxidant capacity of the spleen by activating the nuclear factor erythroid 2-related factor 2 (Nrf2)-activated antioxidant defense system. Notably, the results of PCA and network correlation analysis indicated that XJZ and JSS treatment altered the expression profiles of inflammatory and antioxidant-related factors in the spleen of weaned-piglets, which may involve the synergy of NF-κB and Nrf2 signaling pathways. In summary, our study showed that TCM prescriptions, XJZ and JSS could ameliorate inflammatory response and antioxidant capacity in the spleen by synergistically regulating NF-κB and Nrf2 signaling pathways in piglets.